1984
DOI: 10.1111/j.1600-0609.1984.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thymidine Kinase in Vitamin B12Deficiency

Abstract: In DNA synthesis deoxythymidine kinase (TK) catalyses the conversion of deoxythymidine to deoxythymidine monophosphate (dTMP) via the ‘salvage pathway’. Serum deoxythymidine kinase (S‐TK) was measured in this study in 75 patients with vitamin B12 deficiency by a new, very sensitive method, using 125I‐deoxyuridine as substrate. Elevated S‐TK levels were found in those patients who had developed haemolysis and anaemia and the more advanced the disease the higher the S‐TK value. Thus there was a highly significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thymidine kinase 1 is increased in highly proliferative cells. Although most commonly associated with neoplastic disease, human studies have identified increased in serum TK1 in with patients with hemolytic disease . In a similar fashion, TK1 activity was increased in dogs with IMHA and concentrations of TK1 declined with control of disease as indicated by resolution of hemolysis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thymidine kinase 1 is increased in highly proliferative cells. Although most commonly associated with neoplastic disease, human studies have identified increased in serum TK1 in with patients with hemolytic disease . In a similar fashion, TK1 activity was increased in dogs with IMHA and concentrations of TK1 declined with control of disease as indicated by resolution of hemolysis.…”
Section: Discussionmentioning
confidence: 82%
“…TK1 is commonly associated with neoplastic disease . However, increased TK1 activity is documented in humans with hemolysis and erythro‐megakaryocytopoiesis . TK1 may have utility as a marker of disease control in conditions characterized by cellular proliferation, such as immune‐mediated cytopenias.…”
mentioning
confidence: 99%
“…Hagberg et al showed that severe vitamin B12 deficiency caused elevated serum TK1 levels, as the proliferating tissues became unstable in the absence of the vitamin [41]. Chen et al also showed that serum TK1 concentration was useful in health screening as their patients with elevated TK1 concentration had a significantly increased risk of developing malignancies [42].…”
Section: Discussionmentioning
confidence: 99%
“…The serum activity of TK1 is high in the human fetus and remains elevated in maternal blood up to the 39th week of gestation (Bieniarz et al., 1988 ). Increased TK1 activity is also described in patients with vitamin B12 deficiency and kidney failure due to the impaired excretion of the enzyme with urine (Hagberg et al., 1984 ). The effects of age, pregnancy, vitamin B12 deficiency and kidney failure have not been studied in horses so far.…”
Section: Enzymesmentioning
confidence: 99%